A Conceptual Paper on Organizational Stressors Among Higher Education Deans - Alfred Chan Huan Zhi; Mohd Dahlan Hj Malek; Ferlis Bahari (Asian Social Work Journal, 2016)
This is a conceptual paper to study the effects of organizational stressors that may impede the psychological, physiological and behavioral-interpersonal wellbeing of an organizational member. The study reviews literatures on what effects will general stress alter and degrade the psychological, physiological and behavioral-interpersonal wellbeing of an individual exposed to stressors. The final part of this study’s analysis is what constitutes as organizational stressors among studies that focuses specifically on higher education deans. The factors outlined in the paper were analyzed using the theoretical framework of Managerial Stress Cycle (Gmelch, 1991) and Administrative Stress Index (Gmelch, 1982). A conceptual integrative model was developed in regard to these two frameworks. Both these models are appropriate for this inquiry because, it allows the reader to understand what are the effects of organizational stressors towards psychological and physiological health and its consequences. A number of databases such as ebcohost, springer link, science direct, Jstor and emerald were used to acquire literature on the topics. Conclusions from the literature states that health ailments stemming from stressors are evident and may function as a catalyst towards more dangerous diseases. Higher education dean’s experiences with organizational stressors also seem to be evolving, incorporating new contemporary issues not seen in the past.